Asia Pacific Economic Cooperation (APEC) : challenges and tasks for the twenty-first century - Yamazawa, Ippei, 1937-2018 (Pacific Trade and Development Conference series., 2000)
Featuring contributions from distinguished groups of international academic experts, this book is essential reading for all those interested in political and economic developments in the Asia Pacific.